Perspectives on Nigeria's Economic Development Volume I - Dozie, Pascal (Book collections on Project MUSE., 2013)
In the chapters of this book which was first published in 1999, an attempt has been made to examine several aspects of the Nigerian banking and financial systems, capital market, economic development planning, budget and fiscal policy as well as the role of private sector in development.